Identifying risk characteristics using failure mode and effect analysis for risk management in online magnetic resonance-guided adaptive radiation therapy. (July 2022) - Nishioka, Shie; Okamoto, Hiroyuki; Chiba, Takahito; Sakasai, Tatsuya; Okuma, Kae; Kuwahara, Junichi; Fujiyama, Daisuke; Nakamura, Satoshi; Iijima, Kotaro; Nakayama, Hiroki; Takemori, Mihiro; Tsunoda, Yuuki; et al.
Highlights: Failure mode and effect analysis with process map revealed risks. High-risk failure modes and their corrective measures were identified. Hazardous processes and characteristics of the treatment were identified. All failure modes including those identified in previous papers were summarized and compared. Abstract: Background and purpose: Online magnetic resonance-guided adaptive radiotherapy (MRgART) is a new technology of radiotherapy and requires a new quality control program in many aspects. This study aimed to gain a deeper understanding of risks in online MRgART through the application of failure mode and effect analysis (FMEA) for more enhanced and effective quality assurance (QA) programs. Materials and methods: We present an FMEA conducted by a multidisciplinary team with more than two years of experience. A process map describing the whole process of online MRgART was developed and potential failure modes were identified. High-risk failure modes and their potential causes and corrective measures were also identified. Failure modes were classified into three categories, MRgRT, online ART, and conventional RT, to investigate their features. A comparison with previous studies was also conducted to gain a general perspective. Results: In total, 153 failure modes and 49 high risks were identified. Among all failure modes, 51, 63, and 66 were related to MRgRT, online ART, and conventional RT, respectively. The hazardous processes were structure segmentation, treatment planning, and treatment beam delivery. Lists of failure modes identified in this study and previous studies were presented. Based on the results, characteristics and general aspects of the risks were discussed. Conclusion: Exploring the results of the FMEA enhanced our understanding of risk characteristics to improve QA program of online MRgART.